Some Limitations of the Value Concept - Young, Allyn A. (Quarterly Journal of Economics, 1911)
“Exchange value” compared with the abstractions of physical science, 410. — Subordination of price to value in economic theory, 413. — A general medium of exchange implicit in the theory of exchange value, 416. — Value as imputed price, 419. — Methods of imputation, 421. — Imputation of value extended to goods not priced in the market, 423. — The value of a stock depends on the size and nature of the units chosen, 425. — Meaning of “national wealth,” 427.